Dataset on social and psychological effects of COVID-19 pandemic in Turkey - Emre Sari; Gamze Kağan; Buse Şencan Karakuş; Özgür Özdemir (Scientific Data, 2022)
Measurement(s) Social Effects of Covid-19 Pandemic • Psychological Effects of Covid-19 Pandemic • State-Trait Anxiety Inventory • Measurement of Distress Intolerance • Economic Behavior • Usage of debit/credit card • Online Shopping • Stockpiling • Safety perception • Community safety perception • Feeling uneasy in crowded places • Self-rated health • Personal hygiene behaviour • Having a chronic disease • Diagnosed Covid-19 • Working Home office • Demographic Technology Type(s) Survey Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment Nomenclature of Territorial Units for Statistics (NUTS) of Turkey Sample Characteristic - Location Turkey